Guide RNA Repertoires in the Main Lineages of Trypanosoma cruzi: High Diversity and Variable Redundancy Among Strains - Rusman, Fanny (2021)
Trypanosoma cruzi, as other kinetoplastids, has a complex mechanism of editing of mitochondrial mRNAs that requires guide RNAs (gRNAs) coded in DNA minicircles in the kinetoplast. There are many variations on this mechanism among species. mRNA editing and gRNA repertoires are almost unknown in T. cruzi. Here, gRNAs were inferred based on deep-sequenced minicircle hypervariable regions (mHVRs) and editing cascades were rebuilt in strains belonging to the six main T. cruzi lineages. Inferred gRNAs were clustered according to their sequence similarity to constitute gRNA classes. Extreme diversity of gRNA classes was observed, which implied highly divergent gRNA repertoires among different lineages, even within some lineages. In addition, a variable gRNA class redundancy (i.e., different gRNA classes editing the same mRNA region) was detected among strains. Some strains had upon four times more gRNA classes than others. Such variations in redundancy affected gRNA classes of all mRNAs in a concerted way, i.e., there are correlated variations in the number of gRNAs classes editing each mRNA. Interestingly, cascades were incomplete for components of the respiratory complex I in several strains. Finally, gRNA classes of different strains may potentially edit mitochondrial mRNAs from other lineages in the same way as they edit their own mitochondrial mRNAs, which is a prerequisite for biparental inheritance of minicircle in hybrids. We propose that genetic exchange and biparental inheritance of minicircles combined with minicircle drift due to (partial) random segregation of minicircles during kDNA replication is a suitable hypothesis to explain the divergences among strains and the high levels of gRNA redundancy in some strains. In addition, our results support that the complex I may not be required in some stages in the life cycle as previously shown and that linkage (in the same minicircle) of gRNAs that edit different mRNAs may prevent gRNA class lost in such stage.